Meningkatkan Hasil Belajar Melalui Model Pembelajaran Talking Stick pada Siswa Kelas VII SMP Negeri 3 Madiun Tahun Pelajaran 2023/2024 - Lusi Tania; Darmadi Darmadi; Sri Sasmito Djati (Journal on Education, 2024)
Through this research, we aim to evaluate the effectiveness and impact of implementing the Talking Stick Learning model on the learning outcomes of class VII students. This type of research is Classroom Action Research (PTK) using qualitative and quantitative analysis. Classroom Action Research is a research method carried out by teachers in the classroom as part of their role as educators. This research was carried out at SMPN 3 Madiun City, Mangunharjo District, Madiun City in class VII. The data collection technique in this research is through observation sheets and posttest test questions. This research uses Kurt Lewin's cycle model which is carried out in two cycles. The data analysis used is qualitative and quantitative data analysis. The qualitative analysis used is the Miles and Hubberman model which includes: data collection, data reduction, data display, and conclusion drawing/verification data. Based on the results of research regarding improving learning outcomes for class VII students using the Talking Stick Learning model at SMPN 3 Madiun, Kec. Mangunharjo can conclude that there has been an increase in learning outcomes obtained by elementary school students. This is proven by the results of the percentage of completeness scores in the pre-cycle of only 18.75%, where the percentage of completeness is because the teacher has not implemented the Talking Stick Learning model. Then, after the teacher implemented the model and media, there was an increase in learning outcomes, namely in cycle I with a completion percentage of 75.00%. And in cycle II there was an increase again with a percentage of 87.50%. From the results carried out, it is known that the Talking Stick Learning model has an impact on student learning outcomes at SMPN 3 Madiun.